SATB2‐associated syndrome presenting with Rett‐like phenotypes. Issue 6 (19th January 2016) - Lee, J.S.; Yoo, Y.; Lim, B.C.; Kim, K.J.; Choi, M.; Chae, J.‐H.
Abstract : The SATB2 ‐associated syndrome (SAS) was proposed recently, after the SATB2 gene was initially discovered to be associated with isolated cleft palate. This syndrome is characterized by intellectual disability with delayed speech development, facial dysmorphism, cleft or high‐arched palate, and dentition problems. Here, we describe two novel SATB2 sequence variants in two unrelated patients presenting with Rett‐like phenotypes. We performed trio‐based whole‐exome sequencing in a 17‐month‐old girl presenting with severe retardation and Rett‐like phenotypes, which revealed a de novo missense variant in SATB2 (p.Glu396Gln). Moreover, targeted sequencing of the SATB2 gene was performed in a 2‐year‐old girl with severe psychomotor retardation, facial hypotonia, and cleft palate who also exhibited some features of Rett syndrome. A nonsense variant in SATB2 was identified in this patient (p.Arg459*). This study expanded the clinical and genetic spectrum of SAS. SATB2 variants should be considered in cases with psychomotor retardation alone or in any cases with Rett‐like phenotypes, regardless of the typical features of SAS such as cleft palate. Abstract :